The effect of interaction between parity, gestational diabetes, and pregravid obesity on the incidence of preeclampsia. (18th March 2020) - Košir Pogačnik, Renata; Trojner Bregar, Andreja; Lučovnik, Miha; Krajec, Maja; Verdenik, Ivan; Blickstein, Isaac; Tul, Nataša
Abstract: Objective: To examine the effect of parity, prepregnancy obesity and gestational diabetes on the incidence of preeclampsia in singleton pregnancies using a population-based dataset. Methods: We used the national perinatal information system (NPIS) to identify singleton pregnancies complicated by preeclampsia and analyzed dichotomous-independent variables: being obese or normal weight before pregnancy, being primiparous or multiparous, and being without gestational diabetes mellitus (GDM), with GDMA1, or GDMA2. Results: We found a significantly higher incidence of pregravid obesity among primiparas with preeclampsia (OR 1.6, 95% CI 1.55, 1.66). The data indicate that multiparas had always a significantly lower incidence of preeclampsia, regardless if the women had GDMA1, GDMA2 or had no GDM, and regardless of being of normal weight or obese before pregnancy. The data indicate that the incidence of preeclampsia was not influenced by GDM status, irrespective of parity pregravid BMI category. Conclusions: Our data indicate that GDM is not significantly associated with the development of preeclampsia.